(untitled) (Jahangirnagar University Journal of Biological Sciences, 2020)
The purpose of this study was to estimate the tree biodiversity in the Kaptai National Park. The total area of the Kaptai National Park is about 4,564 ha (11,273.08 acres) under the jurisdiction of Rangamati South Forest Division, Rangamati Hill Tracts district. The study was conducted through extensive survey only on the tree species composition in the Kaptai National Park. During the investigation, a total of 65 tree species belonging to 29 families were recorded from the park. Among the plant families, Mimosaceae possessed the highest number of species (7) followed by Meliaceae (6), Ancardiaceae (5), Moraceae (4), Verbenaceae (4), Combretaceae (4), Myrtaceae (4), Dipterocarpaceae (3), Fabaceae (3), Rubiaceae (2), Bombacaceae (2), Caesalpiniaceae (2), Dilleniaceae (2) and Bignoniaceae (2) respectively. There were 15 families which contained single species. Tree species belonging to the family Mimosaceae was dominated in respect to number of species and their population as well. The findings of the present investigation will contribute in the regeneration of tree species in this degraded forest ecosystem and in the protection, conservation and sustainable management of the Kaptai National Park. Jahangirnagar University J. Biol. Sci. 8(2): 71-79, 2019 (December)